Divestiture, Market Valuation, and Strategy - Montgomery, Cynthia A.; Thomas, Ann R.; Kamath, Rajan R. (Academy of Management Journal, 1984)
An empirical study of 78 divestitures examines the relationship between type of divestiture and financial market valuation. It was found that divestitures linked to corporate or business level strategies in company publications were valued positively by the market; divestitures portrayed as the sale of unwanted units in the absence of defined strategic goals were valued negatively.